Strategi Peningkatan Kinerja Badan Perencanaan Pembangunan Daerah Pemerintah Kabupaten Ponorogo - Luhur Apidianto (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2002)
BAPPEDA at regency/city in local autonomy has important position and very strategic. It caused all of the planning process and development in local governmentprocessed 6y that body. Because of that it's very important if BAPPEDA at regency/ city performance need to improve, base on it's mandate, vision and mission. The same as condition at BAPPEDA Ponorogo regency in local autonomy era will always try to improve has performance as a professional planner development institution project stamp. It means BAPPEDA have already worked yet as a professionalplanner institution. This describe about how is the strategy to increase BAPPEDA Ponorogo regenvg performance. Base on research which is use strategic management concept, writer did strategic management analysis strategic issue identification and finally range the strategies. SWOT model analysis explain thet there are problems become strategic issue all at once with are need to notice and hadling quickly and accurately to increase BAPPEDA Ponorogo regency.